From attitudes to action: a multidimensional model for sustainability education - Baierl, Tessa-Marie; Paul, Jürgen; Bogner, Franz X. (Frontiers in Education, 2025)
Despite the growing sustainability challenges faced globally, many individuals engage only minimally in daily sustainability efforts. Although access to information has become more convenient, many people do not actively seek out information on sustainability. However, understanding sustainability is central to continued engagement in sustainable practices. The European initiative NEB | Lab ECO2-Schools addresses this continued disengagement issue by approaching sustainability education more holistically. It integrates knowledge (information about sustainability), attitudes (a driving force for using this knowledge in sustainable engagement), and behaviors (actions to protect or preserve natural environments). Since health, defined as a person’s physical, mental, and social wellbeing, is primary for almost any behavior, the initiative also integrates health promotion. This includes people’s belief in their abilities, coping strategies, and resilience to handle ambiguity and complexity. This is particularly important in sustainability education, as many complex issues may only be solved eventually. Based on data from 794 participants and structural equation modeling, our findings support the foundational role of health promotion in shaping individuals’ attitudes toward nature and environmental attitudes. Both attitudes, in turn, support learning about sustainability and engaging in sustainable behaviors. Researchers and educators may thus consider integrating health promotion with strengthening positive attitudes to support individuals’ consistent, sustainable engagement.